Seismic microzonation studies in the Southern part of Progo River, special Region of Yogyakarta, Indonesia - Ghina Bani Azifah; Teuku Faisal Fathani; Hendy Setiawan (Geoenvironmental Disasters)
Abstract Background There were more than 700 earthquakes with a magnitude of more than 5.0 over the past 100 years in the Special Region of Yogyakarta, Indonesia. Due to the high intensity of seismic activities, it is essential to perform seismic hazard analysis by considering local site effects. Therefore, this study aimed to analyze the peak ground acceleration (PGA) value based on the earthquake scenario of May 27, 2006, with a magnitude of 6.3, which occurred on the eastern side of the Opak Fault. Methods The study was conducted in the southern part of the Progo River, the Special Region of Yogyakarta, using 31 boreholes and 18 microtremor measurement points. The analysis was carried out using four methods: Kanai (In: Proceeding of Japan Earthquake Engineering Symposium 1–4, 1966) equation using microtremor data, deterministic equations with Ground Motion Prediction Equations Next Generations Attenuation West 2 (GMPE NGA West 2), Kanno et al (Bull Seismol Soc Am 96:879–897, 2006) attenuation equation, and probabilistic method referring to the Indonesian Seismic code. Results Results indicated that the highest value of PGA was obtained using the deterministic GMPE NGA West 2 weighted attenuation equation, which varied from 0.475 to 0.549 g. Meanwhile, Kanno et al (Bull Seismol Soc Am 96:879–897, 2006) attenuation equation resulted in values ranging from 0.266 to 0.394 g. In contrast, PGA values obtained through microtremor measurement resulted in a smaller value, in the range of 0.126–0.214 g. Probabilistic analysis in the study area produces values ranging from 0.373 to 0.450 g. Conclusion The location on the central side of the Progo River shows a lower PGA value than the other sides. PGA values will tend to be higher at locations near the earthquake source. The low PGA value that resulted from microtremor analysis was due to the consideration of local site effects in determining earthquake parameters in the study area. Determining the seismic hazard analysis method in infrastructure planning requires a comprehensive analysis by considering various parameters, such as the planning and design objectives, the location proximity to earthquake sources, historical seismic conditions, and the presence of the local site effects.